Ringtones : the next napster? / Mazlina Mahali and Mohd Izan Helmi Mohamed Aslar - Mahali, Mazlina; Mohamed Aslar, Mohd Izan Helmi (2005)
Ringtones is an essential part of a mobile phone. There are many types of ringtones, from the traditional monotones to the latest true tones. The users seem to be excited with the ringtones more than ever as now they can use their favourite songs as their ringtones. However, a question arises here? Does ringtones amount to infringement of copyright of the original songs? This research is meant to answer that question and other questions with regards to the issue of ringtones. Ringtones amount to infringement of copyright of the original songs if it been obtained without the consent of the original authors or the copyright owners. So, in case of infringement, who should then be held liable for the infringement? There are numbers of parties that should be held liable for the infringement, namely the users, the service providers and the distributors. The researchers are of the opinion that all the three parties above are liable in case of infringement by ringtones. There are also other parties that had been discussed on the aspect of liability, but the researchers are of the opinion that these parties are not liable. They are the publishing house or the producers, and the Music Authors Copyright Protection (MACP). The researchers also come out with some suggestions in order to overcome any issues with regards of ringtones.